The Relationship Between Foot and Pelvic Alignment While Standing - Khamis, Sam (J Hum Kinet, 2015)
A normal motion and segmental interrelationship has been determined as a significant factor in normal function. Yet, the relationship between distal segments and pelvic alignment needs further investigation. The aim of this study was to investigate the interrelationship between distal and proximal lower extremity segments while standing and during induced feet hyperpronation. Changes in alignment of the pelvis and lower extremities were measured at a gait laboratory using the VICON 612 computerized motion analysis system. Thirty-five healthy volunteer subjects were recruited. Four randomized repeated-measure standing modes were used: standing directly on the floor and then on three wedges angled at 10°, 15° and 20° to induce bilateral hyperpronation for 20 seconds. A significant (p<0.05) bi-variate relationship was found between the anterior pelvic tilt and thigh internal rotation, in all four standing positions (.41≤r≤.46, in all p<0.014). A combined effect of rotational alignment between segments and the cumulative effect of foot hyperpronation on pelvic tilt revealed that only the shank significantly affected pelvic alignment, acting as a mediator between a foot and a thigh with the thigh having a crude significant effect on the pelvis. When internal rotation of the shank occurs, calcaneal eversion couples with thigh internal rotation and anterior pelvic tilt. It can be concluded that in response to induced hyperpronation, the shank is a pivotal segment in postural adjustment.